2009
DOI: 10.5012/bkcs.2009.30.4.803
|View full text |Cite
|
Sign up to set email alerts
|

Variation in IR and Raman Spectra of CD3CN upon Solvation of InCl3in CD3CN: Distinctive Blue Shifts, Coordination Number, Donor-Acceptor Interaction, and Solvated Species

Abstract: Notable blue shifts of the ν2 C≡N stretching, ν4 C-C stretching and ν8 CCN deformation bands of CD3CN are observed upon solvation of InCl3, resulting from the donor-acceptor interaction. The Raman spectrum in the ν2 region shows further details; at least two new bands emerge on the blue side of the ν2 band of free CD3CN, whose relative intensities vary with concentration, suggesting that there exist at least two different cationic species in the solution. The strong hydrogen bonds formed between the methyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…The C–N stretching modes of the free CD 3 CN molecule are observed at 2263.1 cm –1 . Upon coordination of the nitrile group via the N atom, donation of a nitrogen lone pair from a slightly antibonding orbital occurs.…”
Section: Interaction Of Mofs With Guest Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The C–N stretching modes of the free CD 3 CN molecule are observed at 2263.1 cm –1 . Upon coordination of the nitrile group via the N atom, donation of a nitrogen lone pair from a slightly antibonding orbital occurs.…”
Section: Interaction Of Mofs With Guest Moleculesmentioning
confidence: 99%
“…The C−N stretching modes of the free CD 3 CN molecule are observed at 2263.1 cm −1 . 605 Upon coordination of the nitrile group via the N atom, donation of a nitrogen lone pair from a slightly antibonding orbital occurs. As a result, the C−N modes of CD 3 CN shift to higher wavenumbers: the higher the frequency, the stronger the bond.…”
Section: If An Oh Group Participates In Different Kinds Of Weak H-mentioning
confidence: 99%
“…41,42 The bands at 321, 113, and 94 cm −1 in the Raman spectrum of the In(III)−A336 phase are characteristic for [InCl 4 ] − , as reported at 321, 112, 89 cm −1. 43,44 The band at 291 cm −1 is attributed to [InCl 5 ] 2− , as reported at 293 cm −1 . 45 Although InCl 3 is extracted by Aliquat 336 mainly as [InCl 4 ] − , a small amount of [InCl 5 ] 2− can form, depending on the A336-to-InCl 3 ratio.…”
Section: Resultsmentioning
confidence: 57%
“…The Raman spectrum of the Fe­(III)–A336 phase shows three bands at 333, 134, and 109 cm –1 , respectively, which match very well with the Raman bands of [FeCl 4 ] − at 334, 132, and 112 cm –1 . , The bands at 321, 113, and 94 cm –1 in the Raman spectrum of the In­(III)–A336 phase are characteristic for [InCl 4 ] − , as reported at 321, 112, 89 cm –1. , The band at 291 cm –1 is attributed to [InCl 5 ] 2– , as reported at 293 cm –1 . Although InCl 3 is extracted by Aliquat 336 mainly as [InCl 4 ] − , a small amount of [InCl 5 ] 2– can form, depending on the A336-to-InCl 3 ratio. , The bands at 308, 231, and 156 cm –1 in the Raman spectrum of the Sn­(IV)–A336 phase can be attributed to [SnCl 6 ] 2– , as reported at 307, 239, and 160 cm –1 .…”
Section: Resultsmentioning
confidence: 74%
“…As in the case of aluminum­(III) chloride, InCl 3 forms a layer-based crystal structure composed of an indium­(III) central layer and closely packed chloride anions. Cho and co-workers investigated the solution behavior of indium­(III) chloride in acetonitrile using infrared and Raman spectroscopic methods, finding that there is a decomposition of InCl 3 to an [InCl 2 (CH 3 CN) 2–5 ] + cation and an InCl 4 – anion. Furthermore, by DFT calculations and experimental studies, Yu et al also confirmed that, in 1,2-dichloroethane and toluene solution, InCl 2 + can represent the catalytically active species derived from InCl 3 via the following reaction of the dissociation: 2InCl 3 = InCl 2 + + InCl 4 – .…”
Section: Introductionmentioning
confidence: 99%